Seroprevalencia de Ehrlichia spp, Anaplasma spp, Borrelia burgdorferi y Dirofilaria immitis en caninos de laciudad de Guayaquil - Mena Pérez, Renán (2024)
The aim of this study was to determine the prevalence of Ehrlichia spp, Anaplasma spp, Dirofilaria immitis and the presence of Borrelia burgdorferi in canines from the city of Guayaquil. Blood samples were taken from 220 dogs and analysed using the ELISA technique (Snap 4Dx Plus, Idexx®). In 120 of these dogs the presence of ectoparasites was determined and their blood samples were also analysed by smears to compare the results with those obtained by ELISA. The results were analysed using Chisquare and Fisher’s exact test to determine the risk association and the influence of risk factors (age, sex, and area) based on the Odds Ratio. The Kappa test was performed to determine the agreement between the tests used. The prevalence of Erhlichia spp was 75.4% (166/220), Anaplasma spp 22.8% (49/220), D. immitis 2.3% (5/220) and null for B. burgdorferi. Coinfection of Erhlichia spp and Anaplasma spp (20.9%) and Erhlichia spp and D. immitis (2.3%) was found. No association (p>0.05) was found between these pathogens with respect to age, sex or the area where the animals live. The level of concordance of the Kappa index between the ELISA technique and the blood smear was acceptable (Erhlichia spp = 0.79; Anaplasma spp = 0.91), but a higher sensitivity in the ELISA method.